1986
DOI: 10.1042/bj2380425
|View full text |Cite
|
Sign up to set email alerts
|

The role of polyphosphoinositides and their breakdown products in A23187-induced release of arachidonic acid from rabbit polymorphonuclear leucocytes

Abstract: Stimulation of rabbit polymorphonuclear leucocytes with A23187 causes phospholipase C mediated breakdown of polyphosphoinositides, as evidenced by accumulation of [3H]inositol-labelled inositol bisphosphate and inositol trisphosphate. At the same time the polyphosphoinositides and the products oftheir breakdown, diacylglycerol and phosphatidic acid, label rapidly with radioactive arachidonic acid. Enhancement of polyphosphoinositide labelling is not as great as enhancement of diacylglycerol or phosphatidic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…Although evidence for agonist-induced release and further oxygenation of stored HETEs has not been previously reported with human PMNs, it is well established that incorporated AA can be released and transformed by PMNs exposed to appropriate stimuli (10,19,34). FMLP, PMA, and A23187 each led to the release of label from PI ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence for agonist-induced release and further oxygenation of stored HETEs has not been previously reported with human PMNs, it is well established that incorporated AA can be released and transformed by PMNs exposed to appropriate stimuli (10,19,34). FMLP, PMA, and A23187 each led to the release of label from PI ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The calcium ionophore A23187 stimulates via activation of phospholipase A2 (Meade et al, 1986) and MAC-induced phospholipase activation has recently been demonstrated in glomerular epithelial cells and shown to be calciumdependent (Cybulsky et al, 1988b). Removal of extracellular Ca2' abolishes MAC-induced secretion of arachidonic acid metabolites in neutrophils and monocytes, suggesting a similar mechanism Hansch et al, 1987).…”
Section: Mechanisms Of Induction Of Proinflammatory Effectsmentioning
confidence: 97%
“…Thereafter, arachidonic acid may be metabolized along one of two pathways, the cyclo-oxygenase pathway, widely distributed in mammalian cells and producing prostaglandins or thromboxanes, or the 5-lipoxygenase pathway, restricted to neutrophils, eosonophils, macrophages, monocytes and mast cells, and producing leukotrienes and HETEs (Salmon & Higgs, 1987). A role for calcium in control of these pathways is suggested by the observations that stimulation of the arachidonic acid cascade in macrophages by many stimuli is dependent on the presence of extracellular calcium and is inhibited by calcium antagonists like quinine (Aderem et al, 1986), and that the calcium ionophore A23187 stimulates arachidonic acid release in neutrophils (Meade et al, 1986). Calcium may be involved at several stages.…”
Section: Mechanisms Of Induction Of Proinflammatory Effectsmentioning
confidence: 99%
“…DAG formation in part through a protein kinase C in rat parotid acinar cells (13). In many cell types, Ca 2+ ionophores and phorbol esters are now known to in crease DAG levels through PC, but not phosphoinosi tide, hydrolysis (12,15,(19)(20)(21). In this study, we showed that both A23187 and PDBu stimulated DAG generation ( Figs.…”
Section: Analysis Of [3h]choline Metabolites Released Into the Mediummentioning
confidence: 60%